Effect of Annealing on the Properties of Antimony Telluride Thin Films and Their Applications in CdTe Solar Cells - Zhouling Wang; Yu Hu; Wei Li; Guanggen Zeng; Lianghuan Feng; Jingquan Zhang; Lili Wu; Jingjing Gao (International Journal of Photoenergy)
Antimony telluride alloy thin films were deposited at room temperature by using the vacuum coevaporation method. The films were annealed at different temperatures in N2 ambient, and then the compositional, structural, and electrical properties of antimony telluride thin films were characterized by X-ray fluorescence, X-ray diffraction, differential thermal analysis, and Hall measurements. The results indicate that single phase antimony telluride existed when the annealing temperature was higher than 488 K. All thin films exhibited p-type conductivity with high carrier concentrations. Cell performance was greatly improved when the antimony telluride thin films were used as the back contact layer for CdTe thin film solar cells. The dark current voltage and capacitance voltage measurements were performed to investigate the formation of the back contacts for the cells with or without Sb2Te3 buffer layers. CdTe solar cells with the buffer layers can reduce the series resistance and eliminate the reverse junction between CdTe and metal electrodes.